(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Pregnancy is an important time period during reproductive cycle of every woman. WHO has set about certain guidelines, in the care of pregnant ladies it’s called as Antenatal care The main aim of this care is to provide an uneventful antenatal period and there by producing a healthy offspring. Intrapartum period also plays a major role in determining the health status of both mother and fetus. Most of the discomforts in the mother can be directly visualized as well as interrupted from her vitals. But in the case of fetus the intrauterine discomforts can be interrupted only from assessing the fetal heart rate. When the fetal heart rate rises above 160/min it is called as fetal tachycardia. This rise in FHR can affect both mother as well as the fetus. The cause should be identified as early as possible and prompt management should be provided. Yoga provides physical as well as mental wellbeing through a holistic approach. It comprises of Pranayama and Asanas which can bring positive effect on the health status of the pregnant woman as well as results in the good outcome of labor. The main reason for tachycardia here was maternal anxiety and stress. Intranatal yoga works very efficiently here and thereby corrects the fetal tachycardia